Combined axial and lateral stability behavior of random checkerboard reinforced cylindrical microshells via a couple stress-based moving Kriging meshfree model - Liu, Hongwei; Safaei, Babak; Sahmani, Saeid (Archives of Civil and Mechanical Engineering, 2022)
In this investigation, a size-dependent numerical solution methodology is devised to analyze nonlinear buckling and postbuckling of cylindrical microsized shells made of checkerboard randomly reinforced nanocomposites subjected to a combination of axial and lateral compressions. To accomplish this purpose, the modified couple stress elasticity continuum is formulated within the third-order shear flexible shell model. Using a probabilistic-based homogenization plan in conjunction with the Monte-Carlo simulation, the effective mechanical parameters of the randomly reinforced nanocomposites are captured. The established size-dependent problem is then numerically solved via using the moving Kriging meshfree technique having the ability to enforce the required boundary conditions straightly at the associated nodes without using any type of penalty technique. By tracing the nonlinear stability paths, it is revealed that for the both axial dominated and lateral dominated loading cases, the stiffening feature related to the rotation gradient tensor causes that the microshell endures higher shortening before the buckling phenomenon occurs. In addition, it is found that by increasing the length to width ratio of graphene nanofillers, the effect of combination of axial or lateral load increases a bit.